English teachers’ epistemic beliefs and metacognitive knowledge about teaching thinking skills for English language learners at an international secondary school - Tahsildar Tehrani, Seyed Hesameddin (2020)
Thanks to the recent attention to thinking skills in the context of English as a Second/Foreign language, many studies have been. However, there is a dearth of studies on English teachers at secondary schools and their metacognition, epistemic beliefs, along with their approach to developing and teaching thinking skills. Thus, this research aimed at studying teaching thinking skills among teachers of English as a First language at an international secondary school in Kuala Lumpur, Malaysia. The objectives of the study, a descriptive case study, are to explore English language teachers’ approach to teaching thinking skills and their metacognitive knowledge of teaching thinking skills as well as their epistemic beliefs about knowledge and learning of thinking skills. The data was collected through interviews with the selected teachers, class observation, video-recording teaching sessions, and video stimulated recall interviews. The findings show that the participating teachers exposed learners to cognitively loaded activities, yet their epistemic views and declarative metacognitive knowledge were different in addition to the nature of cognitive engagements of learners. While some thinking skills were stimulated through collaboration and group work suitable for language learning contexts, the others were individually engaged in class activities that required thinking with little or no group work and oral communication. It was found that sophisticated epistemic beliefs and declarative knowledge of the person ( learner) coexisted in teachers who encouraged group work and communication, and more straightforward and naïve epistemic beliefs and declarative knowledge of affective and memory strategies were identified in the teacher who highlighted individual engagement in the given tasks. The teachers with sophisticated epistemic beliefs were metacognitively aware of the learners and their needs and lack in learning; they were able to predict learning challenges and provide suitable teaching decisions that resulted in communication. This is where the students’ involvement in thinking skills was achieved by asking various WH questions, providing a psychologically safe learning environment, promoting metacognitive strategies, and collaborative lesson tasks. However, naïve epistemic beliefs, insistence on precision, little wait-time, long teacher-talk time, and the teacher’s attention to their teaching procedural knowledge were found together. Hence, despite the cognitive orientation of the introduced activities, the students were would not need to communicate with peers as an ingredient of task fulfillment. The current results indicate that holding sophisticated epistemic beliefs is crucial in developing thinking skills in the L2 context. One implication is that sophisticated beliefs in ESL / EFL teachers can be developed by creating declarative knowledge about the learner through keeping a journal of goals coordinated with the ongoing needs and difficulties learners, curriculum goals, and the success of learners in achieving those goals. Moreover, the results indicated that the novice teacher mainly used the procedural knowledge of teaching which according to the literature (Mackenzie, 2018) is acquired in the teacher education course that she was undergoing with little understanding of the underlying theories. Hence, the current teacher training syllabuses can be developed by providing chances for trainees to reflect on the learning theories and declarative knowledge of teaching strategies.